Pengaruh Kualitas Produk Dan Psikologi Konsumen Terhadap Keputusan Pembelian Pada UMKM Dapur Opat - Rizky Wahyu Pratama; Enjang Suherman; Laras Ratu Khalida (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2024)
The phenomenon that occurs in MSMEs is that there are several consumers who have made purchases but after some time do not make purchases again from the Dapur Opat MSMEs. The aim of this research is to examine product quality and consumer psychology regarding purchasing decisions at Dapur Opat MSMEs. The method used in this research is descriptive quantitative, data collection methods using questionnaires and Likert scales. The population in this study were consumers from Dapur Opat MSMEs, the sample used was 97 respondents, in data analysis. Multiple linear regression analysis technique with a significance level of 0.05. The entire analysis was calculated using the SPSS version 23 program. The test results show that (1) partially product quality has a significant positive effect on purchasing decisions at Dapur Opat MSMEs. (2) partially consumer psychology has a significant positive effect on purchasing decisions at Dapur Opat MSMEs. (3) simultaneously product quality and consumer psychology have a positive and significant effect on purchasing decisions. So, Dapur Opat MSMEs must be able to maintain product quality and provide good consumer psychology to improve consumer purchasing decisions.